2022
DOI: 10.3390/app12104931
|View full text |Cite
|
Sign up to set email alerts
|

Novelty Detection with Autoencoders for System Health Monitoring in Industrial Environments

Abstract: Predictive Maintenance (PdM) is the newest strategy for maintenance management in industrial contexts. It aims to predict the occurrence of a failure to minimize unexpected downtimes and maximize the useful life of components. In data-driven approaches, PdM makes use of Machine Learning (ML) algorithms to extract relevant features from signals, identify and classify possible faults (diagnostics), and predict the components’ remaining useful life (prognostics). The major challenge lies in the high complexity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…[16] or Ref. [17]. Generally, the Supervised/Unsupervised choice depends on how much and which type of data has been collected.…”
Section: State-of-art and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] or Ref. [17]. Generally, the Supervised/Unsupervised choice depends on how much and which type of data has been collected.…”
Section: State-of-art and Related Workmentioning
confidence: 99%
“…Papers such as Refs. [5], [17], or [25] have worked on this topic, framing this as a new research field to help companies implement a preliminary framework to collect data until a real PdM infrastructure is built. This detection type can be applied in numerous domains such as medical, robotic/industrial, vision surveillance, and other fields, as reported in Ref.…”
mentioning
confidence: 99%
“…The authors of [9,10] proposed unsupervised anomaly detection methods using a convolutional approach coupled to an autoencoder framework. In addition, hybrid methods combining a convolutional neural network (CNN) and long short-term memory (LSTM) have been increasingly proposed, such as [10][11][12][13]. A graph neural network (GNN) considers correlations among sensors and hidden relationships within multivariate time series, and it has also found application in the domain of anomaly detection [14][15][16].…”
Section: Related Workmentioning
confidence: 99%
“…This will result in some form of novelty score, which is then compared with a decision threshold, where new unseen inputs are classified as novel if the threshold is exceeded. Novelty detection has gained much research attention, especially in diagnostic and monitoring systems [ 10 , 11 , 12 ]. An overview of the existing approaches is provided in [ 13 ].…”
Section: Related Workmentioning
confidence: 99%